Design Approach To High Voltage High Power Steam-Turbine Driven Alternator - Pritish Kumar Ghosh; Alok Kumar Shrivastav; Pradip Kumar Sadhu; Amarnath Sanyal (Institute of Advanced Engineering and Science, 2016)
The paper deals with the design methodology of high voltage high power alternators driven by steam turbines. These alternators run at a high speed of 3000 rpm in most part of the world (at 3600 rpm in USA) and are of cylindrical pole construction. The design procedure suggested in the text-books of design does not well-suit for large alternators of modern time. Modern high power alternators are designed with a low value of SCR to reduce the size, inertia and cost of the rotor. The diameter is limited by the consideration of centrifugal stresses. The no.of stator slots are determined by the no. of turns. The ventilating circuit has to be designed for hydrogen as coolant and in addition with water flowing through hollow conductors, if required. The data for the design variables and the design constraints are quite different from those for small power ratings. The materials to be chosen must be of very high quality. The computer programme has been chalked out and the case-study has been conducted keeping all these points in view.